Eksistensi Sanad Terhadap Periwayatan Hadis - Saputra, Edriagus; Johendra, Meki; Irfan, Rengga; Fitri, Aulia; Nasution, Azhar (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This research discusses the existence of the sanad in hadith narration and its role in maintaining the authenticity of hadith in Islam. authenticity of hadith in Islam. Using a qualitative method based on library qualitative method based on library research, this study collected data from hadith books, books, articles, journals, and various hadith applications and websites. The data were classified and analysed using academic platforms such as Google Scholar, Publish or Perish, Sage Journal, and Dimensions, and data analysis applications such as Scispace, Dimensions, and VosViewer to identify thematic linkages in previous studies. in previous studies. The results showed that the sanad is a fundamental element in the science of hadith that serves as a verification tool of the verification tool of the validity of a narration. The sanad is classified based on the continuity of the narration, the quality of the narrators, and the number of narrators in each level. The scholars use the i't?b?r sanad method to test the authenticity of the hadith by comparing the various transmission routes. by comparing the various lines of transmission to ensure that there are no weaknesses that could reduce the credibility of the hadith. weaknesses that may reduce the credibility of the hadith. In addition to the classical methods such as Rijalul Hadith, Jarh wa Ta'dil, and talaqqi, modern Muslim scholars have also developed new approaches. modern Muslim scholars have also developed new approaches, such as the digitisation of hadith digitisation of hadith manuscripts, utilisation of artificial intelligence (AI), as well as academic research to maintain the authenticity of the sanad. Despite facing challenges such as the spread of false traditions and distortion of transmission, the combination of traditional methods and modern technology allowed the validity of the hadith to be maintained. With Thus, this study confirms that the sanad serves not only as a historical verification tool, but also as the main instrument in maintaining the purity of Islamic teachings sourced from purity of Islamic teachings that originated from the Prophet Muhammad.